The viability of lytic bacteriophage ΦD5 in potato-associated environments and its effect on Dickeya solani in potato (Solanum tuberosum L.) plants. - Robert Czajkowski; Anna Smolarska; Zofia Ozymko (PLoS ONE)
Dickeya solani is one of the most important pectinolytic phytopathogens responsible for high losses in potato, especially in seed potato production in Europe. Lytic bacteriophages can affect the structure of the host population and may influence spread, survival and virulence of the pathogen and in consequence, infection of the plant. In this study, we aimed to acquire information on the viability of the broad host lytic bacteriophage ΦD5 on potato, as well as to apprehend the specific effect of this bacteriophage on its host D. solani type-strain in different settings, as a preliminary step to target co-adaptation of phages and host bacteria in plant environment. Viability of the ΦD5 phage in tuber extract, on tuber surface, in potting compost, in rainwater and on the leaf surface, as well as the effect of copper sulfate, were examined under laboratory conditions. Also, the interaction of ΦD5 with the target host D. solani in vitro and in compost-grown potato plants was evaluated. ΦD5 remained infectious in potato tuber extract and rain water for up to 72 h but was inactivated in solutions containing 50 mM of copper. The phage population was stable for up to 28 days on potato tuber surface and in potting compost. In both, tissue culture and compost-grown potato plants, ΦD5 reduced infection by D. solani by more than 50%. The implications of these findings are discussed.